Contributing to collective global targets for youth through CGIAR research and innovation - GENDER Impact Platform (CGIAR GENDER Impact Platform, 2024)
The CGIAR GENDER Impact Platform (GENDER) recognizes youth as agents of change in agrifood systems. This position is rooted in the understanding that young people—currently the largest generation in history—are pivotal in shaping social and economic development, including the future of agriculture. GENDER emphasizes the importance of investing in and enhancing the potential of youth as a vital aspect of its agricultural research for development (AR4D) initiatives. This makes youth an ongoing priority target group and a key development partner for CGIAR.